2007
DOI: 10.1364/oe.15.014673
|View full text |Cite
|
Sign up to set email alerts
|

Reflection and emission properties of an infrared emitter

Abstract: The reflection and emission properties of an infrared emitter, which is a plasmonic multilayer structure consisting of a relief metallic grating, a waveguide layer, and a metallic substrate are investigated both experimentally and theoretically. A localized surface plasmon polariton (SPP) mode which is angular-independent in almost the full range of incident angles is observed. The thermal emission of this structure is also measured. It is found that the emission peak coincides with the angular-independent loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Any actual macroscopic thermal body cannot emit more thermal radiation than a blackbody. The Stefan-Boltzman law provides an important theoretical foundation for much of the recent works aiming to design nanophotonic structures in order to tailor the spatial and spectral properties of far-field thermal emission [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Any actual macroscopic thermal body cannot emit more thermal radiation than a blackbody. The Stefan-Boltzman law provides an important theoretical foundation for much of the recent works aiming to design nanophotonic structures in order to tailor the spatial and spectral properties of far-field thermal emission [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Studies have shown that [1][2][3] there is a main factor that causes the energy loss of solar cells. The light absorbed by the solar cells whose energy are lower than its gap can not produce electron-hole pairs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the emissive and absorptive properties of these devices often need to be modified to fulfill particular application requirements-such as gas species selectivity. Several solutions have been proposed including "black" coatings, 11,12 and quarter-wavelength structures, 13,14 in addition to plasmonic [15][16][17][18][19][20] and photonic crystal structures. [21][22][23][24][25] In this paper, we report on a reproducible post-process based on micro-inkjet deposition of graphitic carbon nanomaterial adlayers to augment the IR emissivity of fully CMOS compatible micro-electro-mechanical IR light sources, which we have theoretically and experimentally investigated.…”
Section: Introductionmentioning
confidence: 99%